Conformation and protein interactions of intramolecular DNA and phosphorothioate four-way junctions. Issue 6 (March 2021) - Troisi, Maria; Klein, Mitchell; Smith, Andrew C; Moorhead, Gaston; Kebede, Yonatan; Huang, Raymond; Parker, Elliott; Herrada, Hector; Wade, Elizabeth; Smith, Samara; Broome, Payson; Halsell, Jonah; et al.
The objectives of this study are to evaluate the structure and protein recognition features of branched DNA four-way junctions in an effort to explore the therapeutic potential of these molecules. The classic immobile DNA 4WJ, J1, is used as a matrix to design novel intramolecular junctions including natural and phosphorothioate bonds. Here we have inserted H2-type mini-hairpins into the helical termini of the arms of J1 to generate four novel intramolecular four-way junctions. Hairpins are inserted to reduce end fraying and effectively eliminate potential nuclease binding sites. We compare the structure and protein recognition features of J1 with four intramolecular four-way junctions: i -J1, i -J1(PS1), i -J1(PS2) and i -J1(PS3). Circular dichroism studies suggest that the secondary structure of each intramolecular 4WJ is composed predominantly of B-form helices. Thermal unfolding studies indicate that intramolecular four-way junctions are significantly more stable than J1. The Tm values of the hairpin four-way junctions are 25.2° to 32.2°C higher than the control, J1. With respect to protein recognition, gel shift assays reveal that the DNA-binding proteins HMGBb1 and HMGB1 bind the hairpin four-way junctions with affinity levels similar to control, J1. To evaluate nuclease resistance, four-way junctions are incubated with DNase I, exonuclease III (Exo III) and T5 exonuclease (T5 Exo). The enzymes probe nucleic acid cleavage that occurs non-specifically (DNase I) and in a 5ʹ→3ʹ (T5 Exo) and 3ʹ→5ʹ direction (Exo III). The nuclease digestion assays clearly show that the intramolecular four-way junctions possess significantly higher nuclease resistance than the control, J1.